The effect of beta-neurofeedback on beta-bursts in Parkinson’s disease patients as evidenced through deep brain recordings - Bichsel, Oliver; Bacchi, Stephen; Hajiabadi, Mohammad Mehdi; Schmidt, Franziska; Stieglitz, Lennart (Neurophysiologie clinique, 2026)
Objectives - Increased beta-oscillations (13-35 Hz) in the basal ganglia have been linked to Parkinsonian motor symptoms. Deep brain stimulation (DBS) approaches have been proposed to mitigate pathological beta-activity, with some leading to a global suppression of this activity and others selectively trimming beta-bursts leading to a redistribution of beta-bursts towards shorter, more physiological, durations. Recently, DBS electrode-guided neurofeedback has been explored as an alternative, endogenous technique enabling patients to acquire mental strategies to modulate ongoing subthalamic beta-activity. Here, we investigated the effect of DBS-neurofeedback on beta-burst prevalence, amplitude, and duration. - Methods - We characterised the local field potential (LFP) in the subthalamic nucleus (STN) in terms of beta-burst prevalence, amplitude and length during DBS electrode-guided neurofeedback-modulation of ongoing subthalamic beta-activity. - Results - We previously showed that a cohort of eight Parkinson’s disease (PD) patients with externalised DBS electrodes was able to volitionally control ongoing beta-oscillatory activity by visual neurofeedback within minutes of training, which was also accompanied by an improvement in motor performance. Here, we additionally demonstrate a decrease in beta-burst (> 0.1 s) durations, amplitude and prevalence when transitioning from rest to downregulation after neurofeedback-learning. In addition, downregulation vs. upregulation also resulted in shorter and lower amplitude beta-bursts (>0.1 s) after neurofeedback. - Discussion - DBS electrode-guided neurofeedback enabled patients with PD to exert control over subthalamic beta-oscillations, with downregulation in particular leading to a redistribution of beta-burst characteristics towards more physiological states. This technique may represent a complementary approach to existing DBS strategies by providing patients with an endogenous means of modulating pathological beta-activity.